Hardware-Level Side-Channel Attack Mitigation for PUF-Based Authentication in Smart Cities - Breesam, Wafaa Mohammed; Ridha, Wafaa Mohammed; Hameed, Hayder Ali; Al-Shareeda, Mahmood A.; Almaiah, Mohammed Amin; Shehab, Rami (Engineering, Technology & Applied Science Research, 2025)
Smart city infrastructure requires robust authentication mechanisms, yet existing lightweight techniques lack sufficient resistance to Side-Channel Attacks (SCAs) and biometric noise. This work presents a new authentication protocol that integrates a dual-Physically Unclonable Function (PUF) architecture with biometric binding, fuzzy extractors, response masking, and challenge randomization to strengthen immunity against SCA. Formal security analysis under the Real-Or-Random (ROR) model guarantees session-key secrecy, whereas informal analysis demonstrates resilience against impersonation, replay attacks, and physical-layer information leakage. Simulation results indicate that the recovery rate of the SCA key drops significantly from 84.2% to 6.7%. The protocol provides mutual authentication with an overhead of 2.1 kbit and a latency of 150 ms when supporting 1,000 devices, making it suitable for resource-limited settings. This paper presents a lightweight, secure, and scalable authentication scheme tailored for smart city applications.